Autism spectrum disorder and fetal alcohol spectrum disorder. Part I: A comparison of parenting stress. (June 2013) - Watson, Shelley L.; Coons, Kelly D.; Hayes, Stephanie A.
Abstract Background There is a long history of research on parents of children with disabilities, but to the authors' knowledge, no study has compared the stress of parents of children with fetal alcohol spectrum disorder (FASD) to parents of children with autism spectrum disorder (ASD). Method Twenty-five parents of children with ASD and 25 parents of children with FASD completed the Parenting Stress Index – Short Form (PSI-SF) and the Questionnaire on Resources and Stress – Friedrich's Version (QRS-F). Results Although both parent groups reported elevated stress, PSI-SF results indicated that parents of children with FASD were experiencing significantly more stress compared to parents of children with ASD. No significant differences were found between groups on the total QRS-F, but parents of children with FASD had higher scores on the Pessimism subscale. Conclusions The authors call for measures grounded in theory as well as mixed methods research that includes the subjective experience of parents' stress.